Influência de herbicidas em macrófitas aquáticas - Santos, Durvalina Maria Mathias dos [UNESP]; Banzatto, David Ariovaldo [UNESP] (My University, 1998)
The effects of the herbicides atrazine, 2,4-D, glyphosate (direct and rodeo) and trifluralin were determined on the growth and death of fronds of the aquatic macrophytes Spirodela punctata (G.F.W. Meyer) Thompson and Salvinia minima Baker, through three series of concentrations of each herbicide in climatic chamber (3000 lux, 12/12 hours photoperiod, temperature 23 ± 1°C). After seven days, the concentrations of series 1 (0.025, 0.125, 0.625 and 3.125 mg.L -1) inhibited the growth of Salvinia minima. In Spirodela punctata, only the herbicides rodeo and trifluralin caused growth inhibition. These concentrations did not caused death of fronds in the species. The concentrations of series 2 (40, 60, 80 and 100 mg.L -1) of the herbicides 2,4-D, direct e trifluralin decreased growth of Salvinia minima; death of fronds was caused by 2,4-D and trifluralin to Salvinia minima, and by direct and trifluralin to Spirodela punctata. For the series 3 (200, 400, 600, 800 and 1000 mg.L -1), the herbicide 2,4-D caused growth decrease of both species. The herbicides rodeo and trifluralin showed to be the most lethal for both species. The herbicide atrazine caused death of fronds in Spirodela punctata.

Os efeitos dos herbicidas atrazine, 2,4-D, glyphosate (direct e rodeo) e trifluralin foram avaliados no crescimento e morte de frondes das macrófitas aquáticas, Spirodela punctata (G.F.W Meyer) Thompson e Salvinia minima Baker, por meio de três séries de concentrações de cada herbicida em sala climatizada (3000 lux, 12/12 horas claro e escuro e 23 ± 1ºC). Após sete dias, verificou-se que as concentrações da série 1 (0,025, 0,125, 0,625 e 3,125 mg.L-1) inibiram o crescimento de Salvinia minima. Em Spirodela punctata somente o rodeo e trifluralin provocaram inibição do crescimento. Tais concentrações não provocaram morte de frondes nas espécies. As concentrações da série 2 (40, 60, 80 e 100 mg.L-1) dos herbicidas 2,4-D, direct e trifluralin provocaram inibição do crescimento em Salvinia minima. Nessas concentrações a morte de frondes ocorreu com 2,4-D e trifluralin em Salvinia minima, e com direct e trifluralin em Spirodela punctata. Na série 3 (200, 400, 600, 800 e 1000 mg.L-1), o 2,4-D causou declínio no crescimento de ambas as espécies. Rodeo e trifluralin mostraram ser mais letais para as plantas. Atrazine provocou elevado número de mortes de frondes em Spirodela punctata.
Effects of herbicides on aquatic macrophytes
Keywords: Bioindicators; Frond death; Growth; Pesticides; Salvinia minima; Spirodela punctata